Public policy and mortality among indigenous population of Northern America and Australasia - Kunitz, S. J.
tbls.
pp. 647-672
Keywords: Politica Indigenista; Mortalidad; Mortalidad Infantil; Aborigenes; Australia; Canada; Estados Unidos de America; Nueva Zelandia